2020
DOI: 10.21203/rs.3.rs-28881/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Olfactory and Gustatory Dysfunctions In 100 Patients Hospitalized For Covid-19: Sex Differences and Recovery Time In Real-Life

Abstract: Purpose. COVID-19 displays a variety of clinical manifestations; in pauci-symptomatic patients olfactory (OD) and gustatory dysfunctions (GD) may represent the first or only symptom. To date, literature addressing these disorders is scarce. Aim of this study is to investigate the timing of recovery from OD and GD in a real-life COVID-19 population.Methods. We followed up by a phone interview the first 100 patients discharged a month earlier from three Italian non-intensive care wards.Results. All patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 15 publications
(24 reference statements)
2
27
0
6
Order By: Relevance
“…Indeed, recent studies highlight a relatively fast recovery (~15 days) (Dell'Era et al, 2020;Meini et al, 2020), compatible with the observed partial recovery of the OE in hamsters 14 DPI. SARS-CoV-2 is more deadly in men than women (Jin et al, 2020), but this is not clear yet if the anosmia affects both gender equally (Dell'Era et al, 2020;Meini et al, 2020). However, the recovery of olfaction seems longer in women (Dell'Era et al, 2020;Meini et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Indeed, recent studies highlight a relatively fast recovery (~15 days) (Dell'Era et al, 2020;Meini et al, 2020), compatible with the observed partial recovery of the OE in hamsters 14 DPI. SARS-CoV-2 is more deadly in men than women (Jin et al, 2020), but this is not clear yet if the anosmia affects both gender equally (Dell'Era et al, 2020;Meini et al, 2020). However, the recovery of olfaction seems longer in women (Dell'Era et al, 2020;Meini et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…SARS-CoV-2 is more deadly in men than women (Jin et al, 2020), but this is not clear yet if the anosmia affects both gender equally (Dell'Era et al, 2020;Meini et al, 2020). However, the recovery of olfaction seems longer in women (Dell'Era et al, 2020;Meini et al, 2020). As we only studied female hamsters, more experiments are needed to decipher a gender impact of SARS-CoV-2 in the OE.…”
Section: Discussionmentioning
confidence: 95%
“…In our cohort, 64.1% of patients with chemosensory disorders were female. However, Meini et al (2020) showed that women are less likely to develop chemosensory disorders compared with men. Clearly, sex differences in patients with COVID-19 with OD or GD still require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Most symptomatic COVID-19 patients display manifestations such as fever (98.6%), dry cough (59.4%), dyspnea (31.2%), myalgias (34.8%), sore throat (17.4%), diarrhea (10.1%), and other ( 5 ). Olfactory and gustatory dysfunctions are common symptoms, occurring in about 50% of patients and often presenting early in the clinical course ( 6 , 7 ). Low blood pressure values are frequently observed in hospitalized patients: Wang et al ( 5 ) in their cohort reported a median of mean arterial pressure values of 90 mmHg despite 31% of patients having a history of hypertension.…”
Section: Clinical and Laboratory Findings In Patients With Covid-19mentioning
confidence: 99%